Information technology in bio- and medical informatics : 6th International Conference, ITBAM 2015, Valencia, Spain, September 3-4, 2015, Proceedings /: 6th International Conference, ITBAM 2015, Valencia, Spain, September 3-4, 2015, Proceedings. (2015) - Unknown
No abstract available